2007
DOI: 10.1161/01.res.0000261352.81736.37
|View full text |Cite
|
Sign up to set email alerts
|

Fetal-Derived Trophoblast Use the Apoptotic Cytokine Tumor Necrosis Factor-α–Related Apoptosis-Inducing Ligand to Induce Smooth Muscle Cell Death

Abstract: Abstract-Remodeling of the uterine spiral arteries during pregnancy transforms them from high to low resistance vessels that lack vasoconstrictive properties. This process is essential to meet the demand for increased blood flow imposed by the growing fetus. Loss of endothelial and smooth muscle cells (SMC) is evident in remodeled arteries but the mechanisms underlying this transformation remain unknown. This study investigated the hypothesis that fetal trophoblast invading from the placenta instigate remodeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 36 publications
1
88
2
1
Order By: Relevance
“…Studies in vitro have shown that vEVTs can induce VSMC apoptosis. 5,6 Currently there are no reports of apoptosis in remodeling vessels in vivo; and a recent report described the failure to identify apoptotic VSMCs. 9 Using serial immunohistochemistry and dual immunofluorescence, we detected TUNEL-positive nuclei in VSMCs and endothelial cells of arteries exhibiting signs of VSMC disruption and loss (predominantly in stage II).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in vitro have shown that vEVTs can induce VSMC apoptosis. 5,6 Currently there are no reports of apoptosis in remodeling vessels in vivo; and a recent report described the failure to identify apoptotic VSMCs. 9 Using serial immunohistochemistry and dual immunofluorescence, we detected TUNEL-positive nuclei in VSMCs and endothelial cells of arteries exhibiting signs of VSMC disruption and loss (predominantly in stage II).…”
Section: Discussionmentioning
confidence: 99%
“…The dogma is that invasive EVTs, which detach from placental villous columns anchored to the decidua, mediate the destruction of the vascular wall, either from within the vessel (endovascular (v)EVTs) or from the surrounding decidual stroma (interstitial (i)EVTs). In vitro studies demonstrate that isolated trophoblast cells are capable of triggering apoptosis of VSMCs, potentially via trophoblast-derived Fas ligand and tumor necrosis factor-␣-related apoptosis-inducing ligand, 5,6 and EVTs produce matrix metalloproteinases (MMPs) capable of cleaving substrates in the vascular wall. 7,8 However, apoptotic vascular cell death has not been demonstrated in remodeling vessels in vivo 9 and there is accumulating evidence for remodeling events that precede the appearance of EVT.…”
mentioning
confidence: 99%
“…Certain cytokines and growth factors originally identified in the immune system are now known to influence reproduction and embryogenesis. This is the case with tumor necrosis factor ␣, 32 two other TNFSF ligands, ie, LIGHT 33,34 and TRAIL (tumor necrosis factor apoptosis-inducing ligand), 35 and two unrelated cytokines, colony-stimulating factor-1 36 and transforming growth factor-␤. 37 The same is very likely also to be true of the B-cell regulators, BAFF and APRIL.…”
Section: Discussionmentioning
confidence: 99%
“…Trophoblast cells express FasL and secrete its soluble form -sFasL, which interaction with Fas molecule expressed on EC [15,25] leads to the apoptosis of EC. The development of TRAIL-dependent EC apoptosis was also shown [29]. These mechanisms may also be involved in reducing the number of tube-like structures formed by EC cell in the presence of conditioned media of women's placentas.…”
Section: Resultsmentioning
confidence: 89%